BIOFLOTATION STUDY OF COMPLEX GALENA-SPHALERITE ORE FROM BOGOR, WEST JAVA USING CITROBACTER YOUNGAE STRAIN SKC-4 BACTERIA - HUSNI (NIM : 12513008), HALIMATUL
Lead (Pb) dan Zinc (Zn) are the two most used non-ferrous metals in daily basis, after aluminum and copper. Increased demand for base metals such as Pb and Zn worldwide leads to an increase in the exploitation of low-grade ores due to highgrade ores shortage. As an alternative to increasing the value of those low-grade ores, flotation concentration process with microbes as bioreagent was developed to reduce operating costs and also reduce negative impacts on the environment. In this study, complex Pb-Zn ores from Bogor, West Java were studied using bioflotation method with Citrobacter youngae strain SKC-4 bacteria. A series of bioflotation experiments were conducted to study the effect of SKC-4 bacteria as bioreagent on mineral surface properties, as well as the effect on mineral recovery and concentration in various condition. The effect of SKC-4 bacteria on surface properties was studied by studying bacteria-mineral interactions using ZnS, PbS and pure silica which were incubated for seven days in the GBB (Geomikrobiologi, Biomining and Biokorosi) laboratory. Mineral surfaces before and after the interaction were characterized by contact-angle testing, FT-IR (Fourier Transform-Infra Red) Spectroscopy and SEM-EDS (Scanning Electron Microscope-Energy Dispersive Spectroscopy). Bioflotation experiments were carried out using a 1.5 liter Denver flotation cell with several experimental variables: acidity levels (pH 2, 3, 4, 5, 7 and 9), conditioning time (15, 30, 60 and 120 min), and SKC-4 bacterial concentrations (5%, 10%, 20% and 30% inoculum). The experimental result of interaction between PbS, ZnS and pure silica with Citrobacter youngae strain SKC-4 showed that SKC-4 bacteria acts as biocollector for sphalerite mineral, strong biocollector for Pb and as biodepressant for Si. The result became the first hypothesis for a complex orbital bioflotation experiment of Pb-Zn. Based on the result of mineral recovery and concentration analysis, bioflotation experiment with pH variable showed that the highest Pb recovery result is at pH 4, which is 89.24% with 5.96% concentration and Zn recovery is 68.88% with 8.77% concentration. Further bioflotation experiment with conditioning time variable in pH 4 level showed that the highest result with Pb recovery is 85.18% with 4.87% concentration. The highest Zn recovery is at 120 minutes conditioning time, which is 79.23% with 8.93% concentration. Further bioflotation experiment with bacterial concentration variable at pH 4 level and 60 minutes conditioning time showed that the concentration of bacteria and Zn concentration were positively correlated. The highest Zn recovery is at 30% bacteria concentration, which is 77.82% recovery with 8.52% concentration. Meanwhile, the highest recovery of Pb is at 20% bacteria concentration, which is 90.13% with grade 5.25%.